Effects of N fertilization on soil chemistry dynamics in Ferralsols of the High Potential Maize Zone, Kenya - Oluoch, K.C.; Otinga, A.; Njoroge, R.; Mutua, S.; Ouma, T.; Agredazywczuk, P.; Barthel, M.; Six, Johan; Sonja, Leitner; Oduor, Collins; Harris, E. (International Livestock Research Institute, 2025)
Nitrogen-based inorganic fertilizers have been crucial in crop production globally. For a long time, SSA agriculture has been characterised by low fertilizer use and negative nutrient balances. However, recently fertilizer use has increased drastically. Unfortunately, increased use of synthetic N fertilizers alters soil properties directly and indirectly, and N losses to the ecosystem contribute to environmental degradation and climate change. Limited studies have focused on the effect of increased N application rates on agricultural soils in the tropical highlands. It is crucial to investigate and understand N flows in tropical soils to predict potential ecological impacts of increased synthetic N-fertilizer use while meeting the food demand in SSA.